Big Data and records in the Bibliotheca Alexandrina. Issue 1 (1st December 2022) - Ellaban, Nermeen Ibrahim Ali Ibrahim
Abstract : This research aims to review the projects in the Bibliotheca Alexandrina (BA) in the field of Big Data. In addition, it analyses the possibility to use the Big Data tools in the administrative documentary environment to benefit in the future from the vital data included in its records. Through the use of case studies, the author seeks to identify Big Data in the Bibliotheca Alexandrina, its sources, and relation with the BA records. This article concludes that the Bibliotheca Alexandrina is participating in Big Data initiatives through its web environment and projects. Moreover, the BA documentary environment is 72% valid for applying Big Data tools. The author's assessment is limited to the reality of BA paper or digital records only, excluding records 2.0 (or, records concerning social media?). However, in this case the assessment depends on analysing the three BA records; papers, digital and records 2.0 altogether, then, the percentage of the BA documentary environment validity for using Big Data tools is reduced to be 59%. This article recommends that the Bibliotheca Alexandrina improve its technical and regulatory aspects for records so that it does not lose a vital Big Data source in the future. In this regard, Bibliotheca Alexandrina can cooperate with institutions that have experience in dealing with administrative records; considering them as a vital source of Big Data, and to benefit from them by using Big Data tools for extracting information from records.